Overexpression of HER-2 eu receptor protein in Urinary Bladder Carcinoma, An Immunohistochemical Study. - Al-Tereihi, Rawaa G; Kerbel, Hadeel A.; Saheb, Rehab H.; Al-Janabi, As’ad A.; Yasseen, Akeel A. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Bladder carcinoma is one of the most common cancer worldwide, it accounts for 6.5% of all cancers, with highest incidence in industrialized countries .It represents the fourth most common cancer in men and the eighth in women. Bladder carcinoma depends in its pathogenesis on a combination of genetic and environmental factors, these factors produce phenotypic changes that allow normal transitional cells to become cancerous and finally acquire the “malignant phenotype". Many attempts had been tried to explore the role of some genetic abnormalities encountered in bladder carcinoma. It has indicated that many genetic abnormalities may underline the pathogenesis of cancer evolution of urinary bladder like VEGF , P53, Bcl2 and RB, but nowadays a scientific efforts have raised the possible role of Her-2/neu in bladder carcinoma, and the rate of its overexpression in bladder carcinoma is ranging from 2% - 74%. Objective: To estimate immunohistochemical expression of HER-2 eu receptor protein in Urinary Bladder Carcinoma in relation to other parameters; sex grade, pattern of tumor and stage of tumor . Methods: The present work is performed in the Department of Pathology and Forensic medicine, College of Medicine, Kufa University. Formalin fixed, Paraffin-embedded blocks from 60 (43 males and 17 females) patients with urinary bladder carcinoma were included in this study. A group of 12 patients with chronic cystitis were included as a control group. Avidin-Biotin Complex method was employed for immunohistochemical detection of HER-2 eu. Results: HER-2 eu overexpression was positive in 41.6% of urinary bladder carcinoma, while there was no expression in benign bladder tissue (P<0.05). HER-2 eu immunohistochemical staining was positively correlated with, grade and stage of urinary bladder carcinoma (P<0.05). Conclusion: These findings support the role of HER-2 eu in the carcinogenesis of urinary bladder carcinoma regarding behavior, and aggressiveness, and thus HER-2 eu could be considered as a poor prognostic parameter in urinary bladder carcinoma.